Right ventricular morphology and function following stage I palliation with a modified Blalock–Taussig shunt versus a right ventricle-to-pulmonary artery conduit - Wong, James (Eur J Cardiothorac Surg, 2017)
OBJECTIVES: The Norwood procedure for hypoplastic left heart syndrome (HLHS) is performed either via a right ventricle-to-pulmonary artery (RVPA) conduit or a modified Blalock–Taussig (MBT) shunt. Cardiac magnetic resonance (CMR) data was used to assess the effects of the RVPA conduit on ventricular shape and function through a computational analysis of anatomy and assessment of indices of strain. METHODS: A retrospective analysis of 93 CMR scans of subjects with HLHS was performed (59 with MBT shunt, 34 with RVPA conduit), incorporating data at varying stages of surgery from two congenital centres. Longitudinal and short-axis cine images were used to create a computational cardiac atlas and assess global strain. RESULTS: Those receiving an RVPA conduit had significant differences (P< 0.0001) in the shape of the RV corresponding to increased ventricular dilatation (P = 0.001) and increased sphericity (P = 0.006). Differences were evident only following completion of stage II surgery. Despite preserved ejection fraction in both groups, functional strain in the RVPA conduit group compared with that in the MBT shunt group was reduced across multiple ventricular axes, including a reduced systolic longitudinal strain rate (P< 0.0001), reduced diastolic longitudinal strain rate (P = 0.0001) and reduced midventricular systolic circumferential strain (P < 0.0001). CONCLUSIONS: Computational modelling analysis reveals differences in ventricular remodelling in patients with HLHS undergoing an RVPA conduit insertion with focal scarring and volume loading leading to decreased functional markers of strain. The need for continued surveillance is warranted, as deleterious effects may not become apparent until later years.